Enhanced Plastic Deformation Behavior of Zr62Al8Ni13Cu17 Bulk Metallic Glass Matrix Composites Reinforced with SiC Particles - Lee, Jin Kyu; Yi, Seonghoon (Archives of Metallurgy and Materials, 2026)
Zr62Al8Ni13Cu17 bulk metallic glass matrix composites reinforced with SiC particles were fabricated by spark plasma sintering using gas-atomized amorphous powders. The effects of SiC volume fraction on the microstructure and mechanical behavior were investigated. Dense microstructures with uniformly distributed SiC particles were obtained while preserving the amorphous matrix without crystallization. Compression tests demonstrated that the addition of SiC significantly enhanced both strength and plastic deformability. The composite containing 15 vol.% SiC exhibited a compressive strength of 1670 MPa and a total strain of 4.1%. The improved plasticity is attributed to the formation of multiple shear bands, suppression of shear band propagation, and enhanced interfacial stability associated with the viscous flow of the amorphous matrix.